Evaluation of a Novel Smart Capsule Bacterial Detection System Device for Diagnosis of Small Intestinal Bacterial Overgrowth - Lee, Shaoying Nikki; Rahimian, Pejman; Stork, Cheryl; Moshiree, Baharak; Jones, Mitchell; Chuang, Emil; Wahl, Chris; Singh, Sharat; Rao, Satish S. C. (Neurogastroenterology and motility, 2025)
ABSTRACT Background There is a large unmet need for alternative, non‐invasive, and accurate diagnosis of small intestinal bacterial overgrowth (SIBO). The smart capsule bacterial detection system (SCBDS) device contains a targeted sampling technology and an onboard SCBDS assay to detect metabolically active bacteria in the small intestine. Here, we evaluated the agreement of SCBDS assay with duodenal aspiration/culture ex vivo in a multicenter clinical study. Methods Duodenal aspiration was performed in subjects with gastrointestinal symptoms suggestive of SIBO. Aspirated fluid was sent to local and central microbiology labs to evaluate the agreement for detecting bacteria with SCBDS assay compared to the total bacterial count (TBC) reference standard. The performance of SCBDS assay was evaluated using a receiver operator curve, sensitivities, and specificities. Key Results Aspirates from 66 patients were collected and analyzed for TBC and SCDBS assay. The overall agreement between the two assays was 82%–92% across 3 clinical sites. The SCBDS assay had a sensitivity of 67%–100% and a specificity of 90%–97% using either ≥ 103 or 105 CFU mL−1 cutoff. Additionally, there was a good correlation (r = 0.82) for the TBC culture between the local and central labs. Conclusions and Inferences The SCBDS assay showed a high level of agreement with TBC and improved performance compared to other non‐invasive tests. These results demonstrate the potential utility of SCBDS device to aid SIBO diagnosis as a simple and non‐invasive tool that merits further clinical validation. The smart capsule bacterial detection system (SCBDS) device has an onboard assay to detect metabolically active bacteria in the small intestine. Duodenal aspirates from suspected SIBO patients showed a high level of agreement when compared between standard microbiology lab assay and ex vivo SCBDS assay. SCBDS is a promising tool for SIBO detection.